2018
DOI: 10.1108/jmhtep-03-2017-0019
|View full text |Cite
|
Sign up to set email alerts
|

Multi-professional approved clinicians’ contribution to clinical leadership

Abstract: Purpose The purpose of this paper is to explore how multi-professional approved clinicians (MPACs), responsible for the care of patients detained under the Mental Health Act (2007), can enable clinical leadership in mental health settings. Design/methodology/approach A questionnaire was completed by clinical psychology and mental health nursing practitioners in a mental health trust in the UK working towards or having gained approved clinician (AC) status, identifying barriers to implementation of the roles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In addition to being able to qualify via the portfolio route, applicants could also be given the opportunity to undertake a dedicated training pathway, one that is—in some aspects—akin to the clinical developmental roadmap developed for psychiatric trainees. People choosing to continue to proceed via the portfolio route, however, must also be supported adequately by their respective employers—a common key concern highlighted in this study as well as in the works of Ebrahim and Oates et al [ 4 , 5 ]. To enable this there must be sufficient funding made available to NHS trusts to create training posts as well as new non-medical ACs roles for those already qualified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to being able to qualify via the portfolio route, applicants could also be given the opportunity to undertake a dedicated training pathway, one that is—in some aspects—akin to the clinical developmental roadmap developed for psychiatric trainees. People choosing to continue to proceed via the portfolio route, however, must also be supported adequately by their respective employers—a common key concern highlighted in this study as well as in the works of Ebrahim and Oates et al [ 4 , 5 ]. To enable this there must be sufficient funding made available to NHS trusts to create training posts as well as new non-medical ACs roles for those already qualified.…”
Section: Discussionmentioning
confidence: 99%
“…This study highlighted several reasons for this discrepancy, including the training route to becoming a non-medical AC being unclear and laborious for candidates in comparison to medical colleagues. A previous survey by Ebrahim identified additional contributing factors to this difference in numbers, such as a lack of protected clinical time allocated to training by employers [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Participants said they offered service users a better experience as well as shifting the focus of the multidisciplinary team. Ebrahim's (2018) case study of non-medical ACs in one organisation also found that ACs considered that their role gave them increased power and authority, which could be used to offer service users more choice and could influence the therapeutic focus and nature of relationships in their team. Being approved in the statutory role of AC formalised participants' status as clinical leaders.…”
Section: Discussionmentioning
confidence: 99%
“…As 'early adopters' in influential roles, their aptitude for and commitment to distributed leadership may have been a key factor in those individuals putting themselves forward and being approved as ACs. Ebrahim (2018) noted that non-medical ACs described their clinical leadership as driving change and service transformation. Where participants in this study described becoming an AC as a 'natural progression', it may be that they, as early adopters in a vanguard organisation were always going to be at the forefront of new approaches to care and would make the most of any role that enabled them to lead innovation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation